Fecal Incontinence in Older Women: Are Levator Ani Defects a Factor? - Lewicky-Gaupp, Christina (2010)
OBJECTIVE: To compare pelvic floor structure and function between older women with and without fecal incontinence (FI) and young continent women. STUDY DESIGN: Young (YC, n=9) and older (OC, n=9) continent women were compared to older women with FI (OI, n=8). Patients underwent a POP-Q, measurement of levator ani (LA) force at rest (F(LAR)) and with maximum contraction (F(LAC)), and MRI. Displacement of structures and LA defects were determined on dynamic MRI. RESULTS: LA defects were more common in the OI v. the YC (75% v. 11%, p=0.01) and OC groups (22%, p=0.14); women with FI were more likely to have LA defects than women without (OR 14.0, 95% CI: 1.8-106.5). OI women generated 27.0% and 30.1% less F(LAC) v. the OC group (p=0.13) and YC groups (p=0.04). During Kegel, OI absolute structural displacements were smaller than in the OC group (p=0.01). CONCLUSIONS: OI women commonly have LA defects, and cannot augment pelvic floor strength.